2017
DOI: 10.3390/ijms18030566
|View full text |Cite
|
Sign up to set email alerts
|

A Human Antibody That Binds to the Sixth Ig-Like Domain of VCAM-1 Blocks Lung Cancer Cell Migration In Vitro

Abstract: Vascular cell adhesion molecule-1 (VCAM-1) is closely associated with tumor progression and metastasis. However, the relevance and role of VCAM-1 in lung cancer have not been clearly elucidated. In this study, we found that VCAM-1 was highly overexpressed in lung cancer tissue compared with that of normal lung tissue, and high VCAM-1 expression correlated with poor survival in lung cancer patients. VCAM-1 knockdown reduced migration of A549 human lung cancer cells into Matrigel, and competitive blocking experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…It has previously been demonstrated that CD106 is highly overexpressed in lung cancer compared with normal lung tissue, and that it is associated with poor survival. Additionally, the invasive potential of lung cancer cells is significantly weakened by CD106 silencing (57).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that CD106 is highly overexpressed in lung cancer compared with normal lung tissue, and that it is associated with poor survival. Additionally, the invasive potential of lung cancer cells is significantly weakened by CD106 silencing (57).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mesothelium VCAM-1 expression was negatively associated with progression-free and overall survival in patients with epithelium ovarian cancers [ 118 ]. VCAM-1 expression also is upregulated in lung cancers [ 119 ]. In addition, VCAM-1 is overexpressed in colorectal cancer, and is associated with lymph node metastasis, clinical stage, and tumor progression in patients with colorectal cancer [ 120 ].…”
Section: Role Of Vcam-1 In Cancermentioning
confidence: 99%
“…In a previous study, we reported that VCAM-1 is highly overexpressed in lung cancer tissues, and that high VCAM-1 expression is closely associated with the poor survival of patients with lung cancer [ 119 ]. In this study, using the siRNA-mediated knockdown of VCAM-1, we identified VCAM-1 as a key molecule regulating the invasion of A549 lung cancer cells.…”
Section: Role Of Vcam-1 In Cancermentioning
confidence: 99%
“…Vascular cell adhesion molecule-1 (VCAM-1) is also found expressed in LSECs, which participates in tumor-stromal interactions ( 152 ). Downregulation of VCAM-1 is correlated with suppressed lung cancer cell growth ( 153 ), while VCAM-1 knockdown reduces A549 cells’ ability to migrate ( 154 ).…”
Section: Resultsmentioning
confidence: 99%